Recent Advances In Developing Novel Anti-Cancer Drugs Targeting Tumor Hypoxic and Acidic Microenvironments - Li, Weidong; Sun, Xueying (Recent Patents on Anti-Cancer Drug Discovery, 2018)
Background: Solid tumors often contain hypoxic microenvironments due to abnormal vasculatures and outweighing demands of oxygen. Cancer cells rely on anaerobic respiration, leading to sequential acidic microenvironments. Hypoxic and acidic microenvironments cause genetic instability and activate signaling pathways, contributing to cancer progression and therapy resistance, and have become targets for developing novel anti-cancer agents. Objective: This article reviews recent advances in the development of novel anti-cancer drugs targeting hypoxic and acidic microenvironments. Methods: Recent patents and published literature related to anti-cancer agents targeting tumor hypoxic and acidic microenvironments were searched and reviewed. Key termed used in the searching included cancer, anti-cancer drug, neoplasm, clinical trials, tumor microenvironment, hypoxic microenvironment, acidic microenvironment, hypoxia-inducible factors, hypoxia; metabolism; Warburg effect and aerobic glycolysis. Results: A number of Hypoxia-Inducible Factor (HIF) inhibitors have been developed or discovered, but most of them have only exhibited indirect effects on HIFs, and a limited number of drugs are able to directly interfere with mRNA and protein of HIFs, the dimerization of α and β subunits, or the interaction between HIFs and its activators. The development of agents targeting acidic microenvironments focuses on V-ATPase, monocarboxylic acid transporters, Na+/H+ exchangers and carbonic anhydrases. Proton pump inhibitors as V-ATPase inhibitors have been applied in treating various tumors as an adjuvant therapy, but none of the other inhibitors has been approved for cancer treatment. Conclusion: Developing more specific agents, and seeking sensitive, applicable and accurate biomarkers may improve the efficacy of drugs targeting hypoxic and acidic microenvironments.
Keywords: Acidic microenvironment